2015
DOI: 10.1371/journal.pgen.1004653
|View full text |Cite
|
Sign up to set email alerts
|

Abscission Is Regulated by the ESCRT-III Protein Shrub in Drosophila Germline Stem Cells

Abstract: Abscission is the final event of cytokinesis that leads to the physical separation of the two daughter cells. Recent technical advances have allowed a better understanding of the cellular and molecular events leading to abscission in isolated yeast or mammalian cells. However, how abscission is regulated in different cell types or in a developing organism remains poorly understood. Here, we characterized the function of the ESCRT-III protein Shrub during cytokinesis in germ cells undergoing a series of complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
75
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 57 publications
11
75
1
Order By: Relevance
“…Using the frequency of 32-cell egg chambers as a readout for delay in GSC abscission (Figure 4B-C), we performed genetic interaction experiments combining mutations in ribosome assembly factors or eIF4E with those in Shrub. Some egg chambers containing 32 cells were always observed in heterozygous shrb alleles as previously described (Figure 4D; Matias et al, 2015), while 32-cell egg chambers were rarely observed in heterozygous mutants for eIF4E or ribosome assembly factors alone. In contrast, simultaneously lowering the levels of eIF4E and Shrub by combining mutant alleles in double heterozygous flies led to a significant increase in the frequency of 32-cell egg chamber when compared to their single heterozygous siblings.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Using the frequency of 32-cell egg chambers as a readout for delay in GSC abscission (Figure 4B-C), we performed genetic interaction experiments combining mutations in ribosome assembly factors or eIF4E with those in Shrub. Some egg chambers containing 32 cells were always observed in heterozygous shrb alleles as previously described (Figure 4D; Matias et al, 2015), while 32-cell egg chambers were rarely observed in heterozygous mutants for eIF4E or ribosome assembly factors alone. In contrast, simultaneously lowering the levels of eIF4E and Shrub by combining mutant alleles in double heterozygous flies led to a significant increase in the frequency of 32-cell egg chamber when compared to their single heterozygous siblings.…”
Section: Resultssupporting
confidence: 81%
“…Previous work has shown that the speed and outcome of GSC abscission, the last step of cytokinesis leading to physical separation of the two daughter cells, involves the activity of the Endosomal Sorting Complex Required for Transport-III (ESCRT-III) and is regulated by the Chromosomal Passenger Complex (CPC) and Cyclin B (Eikenes et al, 2015; Mathieu et al, 2013; Matias et al, 2015). For instance, increased activity of the CPC subunit Aurora B kinase as well as decreased levels of the ESCRT-III members such as Shrub (CHMP4) or ALIX delays abscission in GSCs, leading to the appearance of ‘stem cysts’ and the formation of abnormal egg chambers containing 32 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have found that shrub is negatively regulated by AurB in female GSCs (Matias et al, 2015). Though our results suggest that AurB activity should promote ESCRTIII function in the testis, it is compelling to speculate that AurB might control the Phase One-Phase Two transition through shrub.…”
Section: Discussionmentioning
confidence: 99%